In a deep blue hour - Stamm, Peter, 1963- (Other Press, 2025)
"A documentary filmmaker uncovers the secrets of an enigmatic author in this subtly enthralling novel from "one of Europe's most exciting writers" (New York Times Book Review). For days, documentary filmmaker Andrea and her team have been waiting for Richard Wechsler in his Swiss hometown. During their first shoots in Paris, the famous writer had not wanted to reveal much about himself, and now the whole film threatens to fail. In the narrow streets and alleys of the village, Andrea searches for traces of Wechsler's life, contrary to their agreement. But it is not until she starts reading his books again that she discovers a clue to a childhood sweetheart who might still be living there. An old love who influenced his whole life, but whom no one ever knew about"--